PENGARUH INFUSIA KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP JUMLAH SEL RADANG DI FARING PADA TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI ASAP ROKOK - Yuli Punomo; Eny Hartadiyati (Universitas PGRI Semarang, 2015)
This reserach aimed to analyze the effect of mangosteen peel infusionin flammatory cells on mice pharynx. The design used RandomizedControl Design Post Test. It analyzed with Kruskal-Wallis nonparametric95%. The results showed inflammatory cells was 157.7 ?é??10.41 for control (P0), 337.5 ?é?? 18.48 for treatments P1, 287.5 ?é?? 11.90to 247.5 ?é?? treatments P2 and P3 19.36 for treatment. The conclusionfor this research was infusion mangosteen peel significantly affectedon the number of inflammatory cells (p<0.05).Keywords: inflammatory cells, infusia mangosteen rind(Garcinia mangostana L), pharynx